PENCATATAN PERKAWINAN TINJAUAN BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN HUKUM ISLAM - Basri Basri (Universitas Borneo Tarakan, 2019)
AbstractThe main problem in this research is, the marriage registration linked to the validity of a marriage according to Law No. 1 of 1974 and the Law of Islam as well as the legal consequences of marriage were not recorded according to Law No. 1 of 1974 and the Law of Islam.This research is penelitianYuridis Normative namely legal research using secondary data sources in the form of literature votes. research that emphasizes the science of law, tried to examine the legal principles that apply in the community and as supporting research carried Normative method.Marriage has been done according to the law of each religion and his belief that (a valid marriage according to religious law) must be registered in order to obtain legal protection. However, registration of marriage it does not specify when the validity of the marriage because of the validity of marriage is at the time held Munurut law of each religion and belief. Registration of marriages serves to record the occurrence of law concerning marriage, as well as the listing on the birth.The legal consequences of marriage were not recorded, although the religion or belief was valid, but the marriage conducted without the knowledge and supervision of employees marriage registrar does not have the force of law is certain. By law, it would be difficult demanding livelihood and legacy of the husband if the husband dies. Additionally wife is not entitled to the property (Gono-gini) in case of separation. The next legal consequences are children from the marriage that can not be listed deemed illegitimate children unless there is recognition of a father or a court decision.Although the validity of marriage is returned to the law of each religion and belief but the registration of marriages should be made legal by the state so that protection can be implemented to the maximum. And registration of marriages should be made at the same time with the implementation of the marriage. Keywords: Registration, Marriage, Validity